Application Value of the Motor Unit Number Index in Patients With Kennedy Disease - Zhang, Shuo; Yang, Xin; Xu, Yingsheng; Luo, Yongmei; Fan, Dongsheng; Liu, Xiaoxuan (Frontiers in Neurology, 2021)
The aim of this study was to evaluate the usefulness of motor unit number index (MUNIX) technique in Kennedy disease (KD) and test the correlation between MUNIX and other clinical parameters. The deltoids, abductor digiti minimi(ADM), quadriceps femoris(QF) and tibialis anterior(TA)were performed bilaterally by MUNIX technique respectively and compared with course of disease. MUNIX sum score was calculated by adding the MUNIX of these 8 muscles. Disability was evaluated using spinal and bulbar muscular atrophy functional rating scale (SBMAFRS).The MUNIX scores of KD were negatively correlated with the course of disease (p<0.05) while the motor unit size index(MUSIX )scores were positively correlated with the course of disease (p<0.05).The MUNIX sumscore was correlated with the SBMAFRS score (r= 0.714, p< 0.05). MUNIX was more sensitive than compound muscle action potential (CMAP) and muscle strength to reflect the neuron loss and axonal collateral reinnervation. MUNIX sumscore is an objective and reliable indicator in reflecting the progression of the disease, it can be a potential choice for the therapeutic clinical trials.MUNIX can assesses the functional motor axonal loss and is correlated with disability. The MUNIX sumscore may be the objective parameter.